Дослідження факторів, що забезпечують стійкість підприємства під час реалізації інноваційних стратегій - Тацій, І.В.; Сафронська, І.М.; Водяник, Р.В. (Вісник економічної науки України, 2022)
Відповідно до процесного підходу стан підприємства визначається певною сукупністю значень його параметрів. Мета може виражатися деяким набором якісних і кількісних показників у тимчасовому інтервалі. Таким чином, метою є сукупність бажаних значень параметрів здійснення функцій, процесів та видів діяльності. Отримана при цьому ієрархія цілей узгоджується з розробленою ієрархією підпорядкованих понять економічного ризику підприємства. Структурний опис полягає у поділі досліджуваного об'єкта на підсистеми та елементи й у наступному встановленні взаємовідносин і взаємозв'язків з-поміж них. Організаційна структура підприємства є функцією як від прийнятої для підприємства системи цілей, і від чинників середовища. Тому доцільно виділяти класи факторів щодо компонентів структури ресурсного потенціалу підприємства. Інформаційний опис полягає у побудові системи інформаційних потоків підприємства, які є основою для прийняття управлінських рішень. Залежно від організаційної структури підприємства класи факторів виділяються за процесами, що протікають в компонентах ресурсного потенціалу. Розглядаючи підприємство у вигляді виробничо-збутової системи, виділимо класи внутрішніх факторів організаційно-управлінського, виробничо-технологічного та фінансово-економічного потенціалів. According to the process approach, the state of the enterprise is determined by a certain set of values of its parameters. The goal can be expressed by some set of qualitative and quantitative indicators in a time interval. Thus, the goal is a set of desired values of the parameters of the implementation of functions, processes and types of activities. The resulting hierarchy of goals is consistent with the developed hierarchy of subordinate concepts of the enterprise's economic risk. The structural description consists in the division of the researched object into subsystems and elements and in the subsequent establishment of relationships and relationships between them. The organizational structure of the enterprise is a function of both the system of goals adopted for the enterprise and environmental factors. Therefore, it is advisable to distinguish classes of factors regarding the components of the resource potential structure of the enterprise. The information description consists in building a system of information flows of the enterprise, which are the basis for making management decisions. Depending on the organizational structure of the enterprise, classes of factors are distinguished by the processes occurring in the components of the resource potential. Considering the enterprise in the form of a production and sales system, we will distinguish classes of internal factors of organizational and managerial, production and technological, and financial and economic potentials. A variety of internal factors characterizes the possibility of failure to achieve the goals of performance of functions by the personnel of the enterprise. It is possible to single out various factors of the system of marketing, logistics, production, accounting and analysis, etc. Each type of internal factors is divided into types of factors. As mentioned, any event in the company's activity can become a risk event, therefore, a type of risk factor, if it does not fit into the planned course of events and has a deviant effect on the company's activity. We emphasize that the identification of types and subtypes of factors is the most difficult stage of the analysis. For methodical purposes, it is expedient to consider the functional and species branches of internal factors. For example, the functional-specific area for the family of internal financial factors includes inflationary, currency, interest, deposit, tax factors, as well as debt and profitability factors.